Beyond the hype: A critical look at the motivations driving automated driving systems research - Erik Almlöf (Transportation Research Interdisciplinary Perspectives, 2024)
Automated driving systems (ADS) have gained sizable attention over the last decade, promising safer, cheaper, and more accessible transportation. However, the discourse driving this research has not been thoroughly explored, with scant qualitative work detailing specific cases. To address this gap, this paper explores the motivations for the societal need for ADS research for the 500 most cited publications in the field, investigating explicit motivations (e.g., accident reduction), writing style, assumed likelihood of outcomes, and the text's tone. Qualitative and quantitative techniques are used, as well as the tool ChatGPT to investigate the large number of texts.The results show that the most common motivation is the emergence itself (‘ADS are coming, so they need to be studied’), followed by potential benefits such as accident reduction, congestion mitigation, increased comfort and productivity onboard, and environmental concerns. The tone of the publications is primarily neutral or slightly positive but with some deterministic descriptions like ‘ADS will lead to’ rather than more cautious language like ‘can’ or ‘may’.The results offer a glimpse rather than a comprehensive overview of the discourse on ADS within the research community. While the analysis might not capture the nuanced perspectives that readers encounter in publications focused on 'impacts', the reviewed publications remain the most cited works in the field, likely affecting the discourse to some extent.